2015
DOI: 10.1007/s11031-015-9514-x
|View full text |Cite
|
Sign up to set email alerts
|

Brief loving-kindness meditation reduces racial bias, mediated by positive other-regarding emotions

Abstract: Brief loving-kindness meditation reduces racial bias, mediated by positive other-regarding emotions Article (Accepted Version) http://sro.sussex.ac.uk Stell, Alexander J and Farsides, Tom (2015) Brief loving-kindness meditation reduces racial bias, mediated by positive other-regarding emotions. Motivation and Emotion, 40 (1). pp. [140][141][142][143][144][145][146][147] This version is available from Sussex Research Online: http://sro.sussex.ac.uk/60181/ This document is made available in accordance with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 25 publications
5
54
0
Order By: Relevance
“…Few studies addressed mindfulness or meditation relating them to implicit attitudes and representations, and many of these studies employed the IAT [33,36,37,39,40,[42][43][44]. Other studies that focused on implicit learning found a negative relationship between dispositional mindfulness and implicit learning and memory, thus suggesting an effect of mindfulness on implicit cognition in terms of erosion of habitual patterns of responding [37,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies addressed mindfulness or meditation relating them to implicit attitudes and representations, and many of these studies employed the IAT [33,36,37,39,40,[42][43][44]. Other studies that focused on implicit learning found a negative relationship between dispositional mindfulness and implicit learning and memory, thus suggesting an effect of mindfulness on implicit cognition in terms of erosion of habitual patterns of responding [37,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, another line of research has started to address implicit prejudices and stereotypes against members of certain stigmatized groups [31]. Recent studies that used the IAT have shown that meditation can reduce implicit bias; in particular, these studies concerned the practice of loving-kindness meditation and implicit bias toward blacks and the homeless [42,43]. Furthermore, other studies focused on mindfulness practice and reductions on implicit age and race bias and discriminatory behavior [44,45].…”
Section: Meditation Implicit Attitudes and Implicit Memorymentioning
confidence: 99%
“…Most recently, contemplative researchers have asked whether meditation may be beneficial in reducing implicit biases that so often result in discriminatory societal structures and behavior. This line of inquiry is still very new, but early findings point to exciting possibilities including reduced implicit bias, increased helping behavior toward outgroups, and reduced discriminatory behavior [50][51][52][53][54]. Taken together, this work highlights the need for continued study of practices that integrate self and other, and calls for greater incorporation of measures that can assess a range of prosocial outcomes.…”
Section: Prosocialitymentioning
confidence: 90%
“…What is relevant for this conversation is that compassion cultivation training, which includes empathy training, has been known to increase altruistic and pro-social behavior (Leiberg, Klimecki, & Singer, 2011) as well as deepen relationships and social connection (Frederickson et al, 2008;Hein et al, 2010;Hutcherson, Seppala, & Gross, 2008;Klimecki, Leiberg, Lamm, & Singer, 2013;Leiberg, Klimecki, & Singer, 2011). Compassion cultivation training has also been known to reduce implicit bias (Kang, Gray, & Dovidio, 2014;Lueke & Gibson, 2014), stereotype threat (Weger, Hooper, Meier, & Hopthrow, 2012), and reduce racial bias (Stell & Farsides, 2016). However, the specific neurological processes related to these findings are yet unclear.…”
Section: Working With Emotional Activity and Regulationmentioning
confidence: 99%